Tensile performance of cast-in headed anchors in ambient-temperature cured fly ash-based geopolymer concretes with varying fracture energies. (1st May 2023) - Karmokar, Trijon; Mohyeddin, Alireza; Lee, Jessey
Highlights: 43% increase in fracture energy resulted in 17% higher concrete cone capacity. Anchors in geopolymer concrete showed cone angle ranging between 16° and 22°. The exponent of hef 1.5 is not suitable in predicting concrete cone capacity. A new modified equation based on the CCD model is proposed. Abstract: The performance of cast-in headed anchors subjected to tensile loading in ambient-temperature cured fly ash-based geopolymer concrete was investigated in this research. Varying sizes of anchors were installed in geopolymer concrete at effective embedment depths ranging between 40 mm and 90 mm. The new experimental results were compared with those of a previous study on the tensile performance of anchors in geopolymer concrete with similar compressive and tensile strengths, but different fracture energy and elastic modulus. The influence on the concrete cone capacity and its angle due to the varying anchor head size ratio and fracture energy were evaluated in detail. A 43% difference in fracture energy between the two geopolymer concrete mixes translated to 17% increase in concrete cone capacity of the tested anchors. Moreover, the obtained results were compared with the existing prediction models, the Linear Fracture Mechanics (LFM), and Concrete Capacity Design (CCD) models, as well as the design models by ACI 318 and AS 3850.1. The results showed that most of the existing models overestimate the concrete cone capacity of anchors tested in this study and the test-to-prediction ratios depend on the effective embedment depth of anchors. After statistical analysis of experimental results, a new modified equation was proposed to extend the use of the existing CCD model to anchors installed in geopolymer concrete studied in this article.